A Cross-Sectional Survey on the Dispensing Practice and its Determinants from the Retailers’ Perspective in Rural Areas of Gazipur - Ahsan, Tamim; Lira, Dilshad Noor; Islam, Md Samiul; Alam, Md Mahbubul; Shamsur Rouf, Abu Shara (Dhaka University Journal of Pharmaceutical Sciences, 2023)
Being the de facto primary healthcare contacts in rural Bangladesh, retail pharmacy shops (RPSs) influence the medication usage by the people. Therefore, identifying dispensing activities of RPSs can be a key indicator of medicine use. The aim of the current study is to explore the drug dispensing practice of retail pharmacists in the rural areas of Gazipur district. A cross-sectional study was designed to find out drug dispensing practice of analgesic, antipyretic, Gastro Esophageal Reflux Disease (GERD), sedative & hypnotic, ED and multivitamin drugs, assess determinants impacting the practice, and acceptance level of retailers’ suggestions. Forty seven RPSs were selected by random sampling out of 92 in rural areas of Gazipur Sadar from the list of registered allopathic RPSs by the Directorate General Drug Administration (DGDA). Dispensers were interviewed with structured validated questionnaire and data was analyzed using ‘Microsoft Office Excel 2016’. Diclofen, Napa extra, Rivotril, Seclo, Niagra and Filwel Gold were reported to be as the highest dispensed brands at that time. The lowest dispensed brands were found to be Apeclo, Zerin, Relaxen, Procap, Adegra and Biovit Gold. Among determinants impacting dispensing practice, ‘prescriber’s choice’ dominated most in Multivitamin (94%), Sedative & Hypnotic (87%), and Analgesic (77%) groups. ‘Dispenser’s choice’ emerged as a primary determinant in the ED drug group (62%) which is alarming. Moreover, an unlicensed foreign brand, Senegra was found to be dispensed in many drugstores. Buyer’s choice (self-medication) was more remarkable in Antipyretic (38%) and GERD drugs (21%). Although only a few of the reported drugs were over-the-counter (OTC), almost all drugs were being dispensed without prescriptions. As per retailers’ perception, buyers did not seem to be much affected by medicine price (72%) indicating that studied drugs’ price is affordable. A total of 66% dispensers were found to suggest an alternative brand in the absence of a sought brand (brand-substitution) implying to the fact that untrained dispensers may potentially influence drug choice and 77% claimed that buyers usually accept their suggestions which is of no surprise considering the reality of our medication buy-sale practice. Retailers’ perspective might be a great tool to understand drug usage scenario on the ground. Effective regulatory and social initiatives can be devised accordingly to strengthen the rational dispensing and use of medicine. Dhaka Univ. J. Pharm. Sci. 22(1): 55-63, 2023 (June)